Maize Growth and Production Response With A Combination Of Microbial Consortium, NPK, and Ortho Salisic Acid - Syaifuddin; Bayu Adirianto; Taufiq Bachtiar (CV. Syntax Corporation Indonesia, 2024)
Corn is one of the most important food crops in the world. Corn has a high nutritional content, such as carbohydrates, proteins, and fats. Corn can also be processed into various food and beverage products. Corn production in Indonesia currently still does not meet national needs, one of the factors that causes this is the low productivity of corn. Various efforts have been made to increase corn productivity, one of which is by using fertilizers. The purpose of this study was to examine the response of corn growth and production with a combination of microbial consortium, NPK, and ortho salicylic acid. This study used experimental research methods. Data collection techniques in this study were carried out by literature study and observation. The data that has been collected is analyzed descriptively. The results showed that the consortium combination of 1 dose of 5 ml + NPK 15 gr + leaf fertilizer 3 ml was significantly different to increase the best growth in leaf area, total plant weight, corn weight, fruit diameter (base and middle). Based on the results of the study, it can be concluded that the consortium combination of 1 dose of 5 ml + NPK 15 gr + Foliar fertilizer 3 ml can increase corn growth and production.